RNA Hypomethylation and Unchanged DNA Methylation Levels in the Cortex of ApoE4 Carriers and Alzheimer's Disease Subjects - Shen, Wei-Bin; Yang, James Jiao; Yang, Peixin (Current Alzheimer research, 2022)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder, and ApoE4 variants are significant risk factors for AD. Epigenetic modifications are involved in AD pathology. However, it is unclear whether DNA/RNA methylation plays a role in AD pathology, and dysregulation of DNA/RNA methylation occurs in ApoE4 carriers. The present study aimed to determine whether dysregulation of DNA/RNA methylation is present in the brains of ApoE4 carriers and AD patients. In this study, postmortem brain tissues from carriers of ApoE4 and ApoE3, from AD and non- AD controls, were used in the analysis of DNA/RNA methylation, methyltransferases, and their demethylases. Immunofluorescence staining indicates that RNA methylation is suppressed in ApoE4 carriers. Further analysis shows that the expression of RNA methyltransferases and an RNA methylation reader is suppressed in ApoE4 carriers, whereas RNA demethylase expression is increased. RNA hypomethylation occurs in NeuN+ neurons in ApoE4 carriers and AD patients. Furthermore, in ApoE4 carriers, both DNA methyltransferases and demethylases are downregulated, and overall DNA methylation levels are unchanged. Our finding indicates that RNA methylation decreased in ApoE4 carriers before AD pathology and AD individuals. The expression of RNA methyltransferases and RNA methylation reader is inhibited, and RNA demethylase is upregulated in ApoE4 carriers, which leads to suppression of RNA methylation, and the suppression precedes the AD pathogenesis and persists through AD pathology.